UiTM Global conducts pre-briefing for NILAM Q2 with liaison officers from faculties and branches - UiTM, UiTM Global (Office of International Affairs (OIA), 2025)
On 17 June 2025, a Pre-Briefing Session for International Data Reporting (NILAM)- Second Quarter (Q2) was held involving liaison officers from faculties, branches, and PTJs across the university. The aim of the session is to ensure alignment and readiness for the upcoming NILAM report